Analysis of the histology of the scar bladder and biochemical parameters of rats with a solitary kidney undergoing immunosuppression with tacrolimus - Cavalli,Ricardo Cavalheiro (2014)
PURPOSE:To evaluate bladder histology in healing and biochemical analysis of rats with single kidney in ischemia/reperfusion, treated with tacrolimus.METHODS: Fifty rats randomized into five groups. Three rats died in surgery, 47 rats divided in groups: Control (non-operated, n=10), Sham (operated without drugs, n=8), T1 (operated + tacrolimus 1mg/kg, n=10), T2 (operated + tacrolimus 0.1 mg/kg, n=10), T3 (operated + tacrolimus 10mg/kg, n=9). The surgery was: laparotomy, right nephrectomy, left kidney ischemia/reperfusion, cystotomy followed by bladder suture. After that, rats were submited to gavage daily (Control and Sham with saline solution. T1, T2, T3 with tacrolimus in doses already mentioned). On the 14th day, after death induction, cystectomy was performed and bladder was histologicaly analysed. The serum urea, creatinine and tacrolimus were analysed too.RESULTS: There was difference in serum tacrolimus in T3 compared to the other groups (p<0.05). There was higher doses of creatinine in T3 group and higher urea in groups with tacrolimus. There were significant differences among all histologic variables comparing groups with and without tacrolimus (p<0.05).CONCLUSION: Tacrolimus associated with ischemia/reperfusion is nephrotoxic, suppresses inflammation and seems to delay the healing bladder.